Training of academics for generational replacement in the Universidad Pedagógica Nacional (Revista INTEREDU11, 2021)
The objective of this research is to learn about the knowledge and competences set in Academics Training Program at Universidad Pedagógica Nacional (UPN for its acronym in Spanish), in order to be prepared for a possible generational replacement. To this end, enquiries related to the profile of academic trainers were raised, and the real need for training of academics, as well as the profile of entities responsible for carrying out this vocational training process were enquired. Both the research instrument –semi-structured interview– and the selection of study subjects were set together on the basis of a hermeneutic-philosophical methodology. The results revealed that the formation of the future UPN academics must be developed in epistemic communities supported and oriented by a scientific paradigm, which are presented as formative suggestions in this study.